AB0222 ASSOCIATION BETWEEN CENTROMERE AND TOPOISOMERASE SPECIFIC IMMUNE RESPONSES AND THE DEGREE OF MICROANGIOPATHY IN SYSTEMIC SCLEROSIS. (June 2019) - Leeuwen, Nina van; Bakker, Jaap; Wortel, Corrie; Scherer, Hans Ulrich; Toes, Rene; Huizinga, Thomas; Vries-Bouwstra, Jeska de
Abstract : Background: In systemic sclerosis (SSc) more severe microangiopathy has been associated with worse disease outcome. In addition, auto-antibodies are important tools for disease prognostication. To what extent these two biomarkers reflect the same pathophysiological background is not clear. A better understanding of the interaction between the specific auto-immune response and the degree of microangiopathy could not only improve our insight in disease pathophysiology but could also contribute to more reliable disease prognostication. We hypothesized that an ongoing activated immune response, as reflected by higher anticentromere antibody (ACA) or anti-topoisomerase (ATA) specific IgG levels and higher number of ACA or ATA specific isotypes, associates with more severe microvascular damage and with more severe SSc. Objectives: 1. To evaluate whether ACA and ATA isotype expression associates with the degree of microangiopathy in SSc. 2. To determine the additive value of more activated immune response for prediction of organ involvement. Methods: ACA and ATA IgG, IgA and IgM levels were measured in serum samples of 129 ACA IgG+ or 102 ATA IgG+ SSc patients, respectively. The degree of microangiopathy was determined based on nailfold videocapillaroscopy (NVC) images, with SSc late pattern reflecting more severe microangiopathy. Associations between ATA and ACA isotype expression and NVC patterns were evaluated. Logistic regression analyses, with NVC pattern, autoantibodies, isotype expression and IgG levels as independent and disease characteristics as dependent variables were performed, adjusted for age, sex and disease duration. Results: NVC images were available for 164 patients (n=100 ACA, n=64 ATA). Prevalence of SSc early, active and late pattern did not differ between ACA/ATA IgM+ and IgM – patients, nor between ACA/ATA IgA+ and IgA – patients. No associations between isotype expression (Figure 1 ) or IgG levels and NVC patterns were found. Logistic regression confirmed the association of ATA with pulmonary involvement (multivariable Odds Ratio [OR] 9.0 range 2.3-34.5) and of late SSc pattern with digital ulcers (multivariable OR 12.0 range 3.0-48.0) and pulmonary involvement (multivariable OR 5.0 range 1.5-16.1). Of note, higher topoisomerase and centromere specific IgG levels were independently associated with presence of digital ulcers (OR 3.5 range 1.1-11.0). Conclusion: We did not observe an association between the quality of the anti-centromere specific or the anti-topoisomerase specific immune response and degree of microangiopathy in SSc patients. This might indicate that specific autoantibodies and stage of microangiopathy reflect different processes in the disease. The association between higher ATA or ACA specific IgG levels with digital ulcers, independent of specific autoantibody and NVC patterns suggests that an ongoing, active immune response is associated with more severe organ involvement. Disclosure of Interests: Nina van Leeuwen: None declared, Jaap Bakker: None declared, Corrie Wortel: None declared, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS, Rene Toes Grant/research support from: Sanofi, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Jeska de Vries-Bouwstra: None declared